2020
DOI: 10.17269/s41997-020-00423-1
|View full text |Cite
|
Sign up to set email alerts
|

A public health timeline to prepare for COVID-19 vaccines in Canada

Abstract: For control of COVID-19, community immunity is required, necessitating widespread immunization. COVID-19 vaccines are coming to Canada, with the government announcing in August 2020 agreements with four different companies for their COVID-19 vaccine if their trials are successful. Never before has public health had to rapidly develop a vaccine introduction program for multiple new but differing vaccines with the added pressure that the program is needed across all ages and in all Canadian communities and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(30 reference statements)
0
15
0
1
Order By: Relevance
“…Firstly, providing reliable COVID-19 vaccine-related information in a clear, transparent, and timely manner can foster public trust in the COVID-19 vaccines [ 35 ]. Experiences in Israel, Canada, and the US indicated that transparent monitoring and reporting of adverse events of COVID-19 vaccines were critical in strengthening public confidence toward COVID-19 vaccinations [ 38 , 39 , 40 ]. Existing studies have highlighted the need for governments to inform the public about both the benefits and harms of receiving COVID-19 vaccinations using data from vaccine trials [ 33 , 35 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, providing reliable COVID-19 vaccine-related information in a clear, transparent, and timely manner can foster public trust in the COVID-19 vaccines [ 35 ]. Experiences in Israel, Canada, and the US indicated that transparent monitoring and reporting of adverse events of COVID-19 vaccines were critical in strengthening public confidence toward COVID-19 vaccinations [ 38 , 39 , 40 ]. Existing studies have highlighted the need for governments to inform the public about both the benefits and harms of receiving COVID-19 vaccinations using data from vaccine trials [ 33 , 35 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, healthcare professionals have to provide person-centered recommendations on COVID-19 vaccinations. They should keep their COVID-19 vaccine knowledge up-to-date by obtaining regular information released from the local government [ 39 , 48 ]. However, healthcare professionals may be overloaded with constantly evolving information [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine roll-out, however welcome, is an additional strain not only in LICs but also increasingly in high-income countries. 21 22 There is a need to support health systems to sustain routine services—this is more critical for weaker health systems seeking to prevent excessive avoidable mortality. 20 Lastly, as countries plan to roll out COVID-19 vaccination, it is important that effective strategies to deal with vaccine hesitancy are developed and implemented.…”
Section: Focus On Implementationmentioning
confidence: 99%
“…Среди большей части населения пока еще происходит естественное формирование невосприимчивости к вирусу в результате заболевания COVID-19, обусловленного пандемическим распространением SARS-CoV-2. Одновременно в ряде стран нарастает масштаб внедрения специфических вакцин, а в ряде случаев начинается массовая вакцинация населения [35,38,40].…”
Section: Introductionunclassified